"It's a New Chapter Now": Establishing Commitments in the Romantic Domain during Young Adulthood. Issue 1 (2nd January 2020) - Larsson, Hanna; Eriksson, Py Liv; Frisén, Ann
ABSTRACT: This longitudinal study examines identity development in the domain of romantic relationships during young adulthood and what the process of establishing commitments without exploration in this domain involves. Identity status in the romantic relationships domain was assessed for 118 Swedish individuals at the ages of 29 and 33, using the Identity Status Interview. Identity diffusion was less common at age 33 than at age 29, whereas foreclosure, moratorium, and identity achievement were equally common at both ages. The majority of those assigned to identity diffusion at age 29 had transitioned to identity foreclosure by age 33. These nine participants were selected as a subsample for further analysis of the process of commitment-making, and changes in their identity narratives between age 29 (before establishing commitments) and age 33 (after establishing commitments) were examined using case-based thematic analysis. The results suggest that the commitment-making process involves changes in identity content, such as having more elaborate and positive views on romantic relationships, as well as changes related to identity processes, including narrating one's experiences and views concerning romantic relationships in a more temporally integrated way.